A novel and efficient immunoglobulin Y extraction method using poloxamer-polyethylene glycol. Issue 7 (9th August 2017) - Li, Cui; Ren, Hao; Schade, Rüdiger; Zhang, Xiaoying
ABSTRACT: Although many IgY extraction methods (such as polyethylene glycol (PEG) precipitation method, octanoic acid method, water dilution method, etc.) have been established, there is still industrial drive and real need in developing scale-up IgY production methods. Some previous studies have reported that poloxamer degreasing method shows very good result in IgY extraction from egg yolk with high degreasing speed, harmlessness, simpleness in operation and minimal effect on antibody titer. In this study, we developed a new method, poloxamer-PEG method, to obtain functional IgY with high purity and yield. First, the delipidation solution was added into the diluted yolk samples, and then the filtrates were collected from the diluted yolk samples after 3 hr in room temperature. PEG-6000 was added into the collected filtrates and the mixture was centrifuged after shaking on the roller mixer for 45 min at room temperature. Last, the precipitates were resuspended in 1 mL phosphate buffered solution (PBS) buffer and dialyzed overnight. The results showed that the total protein concentrate of extractive could reach at 30 mg/mL and the purity of the IgY could reach at 92.71% with the novel method, which was superior to the PEG precipitation method and water dilution method.